Evaluation of Rhizoctonia zeae as a potential biological control option for fungal root diseases of sugar beet. (31st March 2015) - Webb, K.M.; Harveson, R.M.; West, M.S.
Abstract Several common root diseases routinely damage sugar beet in Nebraska and other production areas of the Central High Plains, and it is becoming more common to find fields infested simultaneously with multiple pathogens. Owing to the shortage of available fungicides for economic management of soilborne diseases, alternative techniques such as biological control are increasingly being sought for disease management. Over the last several years, unidentified, sterile fungi have been isolated in conjunction with pathogens from infected sugar beet roots and seedlings. At least two promising isolates have been identified from in vitro assays that inhibit the radial growth of multiple sugar beet root pathogens, including Rhizoctonia solani, Fusarium oxysporum f. sp. betae, Phoma betae and Pythium aphanidermatum. Based on morphological and molecular characterisation, two isolates, 'Hall' and 'R47', were putatively identified as Rhizoctonia zeae. In vitro pathogenicity testing indicated that these isolates were not pathogens of sugar beet. Both isolates were compared with the well‐established biological control fungus Laetisaria arvalis and tested as potential treatments in a field naturally infested with multiple sugar beet root diseases. Data indicated that these fungi provided some level of protection against a complex of soilborne diseases and suggest that these isolates could have a potential fit in an integrative management strategy for several sugar beet root diseases.